Genetic test for the prescription of diets in support of physical activity - Naureen, Zakira; Miggiano, Giacinto Abele Donato; Aquilanti, Barbara; Velluti, Valeria; Matera, Giuseppina; Gagliardi, Lucilla; Zulian, Alessandra; Romanelli, Roberta; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Owing to the fields of nutrigenetics and nutrigenomics today we can think of devising approaches to optimize health, delay onset of diseases and reduce its severity according to our genetic blue print. However this requires a deep understanding of nutritional impact on expression of genes that may result in a specific phenotype. The extensive research and observational studies during last two decades reporting interactions between genes, diet and physical activity suggest a cross talk between various genetic and environmental factors and lifestyle interventions. Although considerable efforts have been made in unraveling the mechanisms of gene-diet interactions the scientific evidences behind developing commercial genetic tests for providing personalized nutrition recommendations are still scarce. In this scenario the current mini-review aims to provide useful insights into salient feature of nutrition based genetic research and its commercial application and the ethical issue and concerns related to its outcome.